Juegos tradicionales en el desarrollo de la velocidad en jóvenes de 14 a 15 años - Bustamante Arevalo, Madelyne Maria (2025)
Traditional games promote enriching learning situations, in addition to promoting emotional and motor progress; This research is focused on the analysis of the impact that traditional games have on the translation of the speed of movement of young people between 14 and 15 years old from the “Técnico Ricaurte” Educational Unit. In the first chapter, the problem to be investigated is contextualized and the general and specific objectives that make the work viable from now on will be defined. The second chapter is focused on exposing the theoretical framework, in which the research variables will be analyzed and will be based on the use of traditional games as physical education tools, as well as the historical background of this topic. Chapter 3 refers to the methodology used during the investigative process, such as methods, techniques and instruments to measure the information obtained. Next, in chapter 4 the results obtained through data collection will be presented, along with their respective analysis and interpretation in statistical graphs and finally, within chapter 5 the conclusions and recommendations to which we have reached are presented, a once the research hypotheses were verified and if the established objectives were met.